2020
DOI: 10.1016/j.ypmed.2020.106281
|View full text |Cite
|
Sign up to set email alerts
|

Stay-at-home orders and firearms in the United States during the COVID-19 pandemic

Abstract: Firearms are a leading cause of death and injury in the United States, and this trend has continued during the COVID-19 pandemic. We sought to identify whether states designated gun retailers as essential businesses in their stay-at-home orders and characterize other references that could affect firearm acquisition during the COVID-19 pandemic. In this cross-sectional policy review, we assessed stay-at-home orders issued in March or April 2020. Orders were reviewed in their entirety, and any reference to firea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A study from the Netherlands found that school closures were associated with a 3-times higher rate of emotional abuse, defined as emotional neglect or witnessing domestic violence 16 . The rise in firearm injuries during the pandemic has been noted in pediatric patients 2 , 11 and adult patients 17 , 18 , 19 , 20 . A rise in firearm sales during the pandemic has also been noted 19 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A study from the Netherlands found that school closures were associated with a 3-times higher rate of emotional abuse, defined as emotional neglect or witnessing domestic violence 16 . The rise in firearm injuries during the pandemic has been noted in pediatric patients 2 , 11 and adult patients 17 , 18 , 19 , 20 . A rise in firearm sales during the pandemic has also been noted 19 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…These trends emerged both in an increase in number of people screening high risk with DA-LE scores, which represent survivors of domestic violence' likelihood of near lethal and lethal violence, and is administered by law enforcement officers, and in the frequency of extreme and severe violence in cases referred to JGCC advocates for services. JGCC and community organizations also observed more firearms being used by abusive partners to threaten survivors, a potential outcome of a massive rise in gun purchases during the pandemic and a nationally reported 35% increase in fire-arm related homicides over previous years (Hoops et al, 2020;Kegler et al, 2022;Kerner et al, 2022;Miller et al, 2022).…”
Section: Pandemic Trendsmentioning
confidence: 99%
“…Gun violence has also been studied, particularly in the USA, either as part of a set of crimes [11,12] or individually [13][14][15]. Most of these studies begin by registering "a surge in gun sales, driven by public panic and unfounded fears" [32] (p.53).…”
Section: Crime During the Pandemicmentioning
confidence: 99%
“…Most of these studies begin by registering "a surge in gun sales, driven by public panic and unfounded fears" [32] (p.53). In this regard, Hoops et al studied the broad availability of weapons and legislation in states such as Missouri and Nevada that guarantee the sale of weapons during states of emergency (2020) [15]. According to a survey conducted by Kravits-Wirtz et al (2020) [33], in California alone, 110,000 people bought weapons in response to the pandemic, of which 47,000 were first-time owners.…”
Section: Crime During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation